Nghiên cứu đánh giá hàm lượng dược chất rotundin của cây Bình vôi phân bố tự nhiên tại tỉnh Thái Nguyên - Dương, Văn Thảo (TẠP CHÍ KHOA HỌC LÂM NGHIỆP, 2024)
The Stephania brachyandra plant, naturally found in Thai Nguyen, is scientifically known as Stephania brachyandra. It belongs to the genus Stephania Lour., family Menispermaceae, order Menispermaceae. This plant is used as a raw material to extract L-tetrahydropalmatine (the active ingredient known as Rotundin) with the chemical formula C21H25NO4. Rotundin is an alkaloid with sedative, sleep-inducing, and memory-reducing effects. The purpose of this study is to evaluate tof Rotundin content in the Stephania brachyandra species and analyze the correlation between the size of the specíe tubers and the content of Rotudin in Stephania brachyandra naturally distributed in Thai Nguyen province. The analysis results show that the content of Rotundin in 160 samples of naturally distributed Stephania brachyandra in Thai Nguyen province ranges from 90.4 to 981 mg/100g. The analysis of the correlation coefficient between tuber diameter and Rotundin content shows a strong relationship between Rotundin content and tuber diameter. This demonstrates diversity in active ingredient content among natural Stephania brachyandra plant samples, thereby confirming their significant potential as a medicinal resource.